Efektifitas Kitosan sebagai Inhibitor Korosi pada Baja Lunak dalam Air Gambut - Erna, Maria; Emriadi, Emriadi; Alif, Admin; Arief, Syukri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
This research is intended to learn inhibition efficiency of mild steel corrosion in peat water using two type ofchitosan. First chitosan is without treatment and the second one is synthesized by ionotropic gelation method andthen is characterized by Fourier transform Infrared spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM).Diameter of chitosan porous is about 500 nm which is measured based on morphological photo using SEM withinhomogeneous porous shape and porous distribution is unsmooth . Effect of chitin and chitosan on the corrosionof mild steel in peat water is studied using weight loss method. It is found that corrosion inhibition efficiencydepends on peat water pH, inhibition technique and interaction time. The results show that inhibition efficiency ofchitosan without treatment and with treatment are 88.73% and 93.32% respectively. The inhibition is assumed tooccur via physicsorption of the chitin and chitosan molecules on the metal surface. The Langmuir adsorptionisotherm is tested for their fit to the experimental data.